THE INITIAL IMPLEMENTATION OF ACCRUAL BASED ACCOUNTING, THE EFFECT ON PERFORMANCE AND FINANCIAL REPORTING QUALITY AT LOCAL GOVERNMENTS IN INDONESIA - Gamayuni, Rindu Rika (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
Abstract: In Indonesia local government, accrual based Government Accounting Standard (GAS) was started to be mandatorily applied in 2015, so this research aims to investigate to what extent the role of accrual GAS implementation toward quality of financial reporting and financial performance especially at local governments. Population of this study is Local Governments of districts/cities in Indonesia for Fiscal Year 2014 and Fiscal Year 2015, as many as 542 local governments (before and after the implementation of accrual base). Sampling method uses probability sampling which is cluster sampling. In this case, the population is divided based on 34 province clusters, so the number of sample obtained is 242 local governments of districts/cities in Indonesia. The hypothesis testing uses paired t test. The object of research is the financial reporting quality and financial performance. The results of this study provide empirical evidence that there is an increase in the quality of financial reporting after the application of accrual-based accounting at local governments in Indonesia, but have not proven the existence of the increased financial performance. There is no differences in financial performance before and after accrual based accounting implementation at local governments in Indonesia. This hyphothesis was not supported due to the application of accrual basis accounting is still in the early stages of implementation (1 year) that still have constraints in limited human resources competencies, necessary adaptations or adjustments in the process of change. Local governments in Indonesia must apply accrual based accounting because it is proven that it increases financial report quality. However, the system implementation in the beginning period found many obstacles so it needs continuous adjustment and learning in order to reach desirable goal. There is still a debate on how important is the implementation or adoption of accrual IPSAS in many countries, including Indonesia. In Indonesia, the implementation of accrual based Government Accounting Standard (SAP/GAS) is new mandatory since 2015. The result of this research will give contribution to the theory, that there is significant influence of implementation accrual based GAS to financial reporting quality, but no significant increase in financial performance (efficiency and effectiveness) at local government. Therefore, this result study will be used to determine related policies about the implementation of accrual based GAS. Keywords: Accrual Based Accounting, Financial Reporting Quality, Financial Performance, Government